2013
DOI: 10.1080/03079457.2012.751485
|View full text |Cite
|
Sign up to set email alerts
|

The required sample size in vaccination-challenge experiments with infectious bronchitis virus, a meta-analysis

Abstract: For statistical, animal welfare and financial reasons the choice of the number of chickens per group in experiments is important. This estimation, together with the number of tracheal organ cultures (TOCs) that need to be examined from each chicken in order to assess protection, should be based on the difference in level of protection that one would like to be able to detect (effect size), the expected variability of the results between and within the chickens, the desired confidence level and the power of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…When vaccinations with a single serotype are not providing sufficient protection against the prevailing field strains, vaccines of other serotypes can be added to the program. The broadening of the protection can be achieved by adding vaccines to the program that are homologous to the most important prevailing field strains (80,81,100,104,108) and/or by using combinations of vaccines that are able to induce a broad cross-protection against many strains (45,63,79).…”
Section: Types Of Vaccinementioning
confidence: 99%
“…When vaccinations with a single serotype are not providing sufficient protection against the prevailing field strains, vaccines of other serotypes can be added to the program. The broadening of the protection can be achieved by adding vaccines to the program that are homologous to the most important prevailing field strains (80,81,100,104,108) and/or by using combinations of vaccines that are able to induce a broad cross-protection against many strains (45,63,79).…”
Section: Types Of Vaccinementioning
confidence: 99%
“…The level of protection of the trachea was determined using the ciliostasis test on five tracheal rings per chicken at 5 days post challenge (De Wit et al, 2013). The level of beating of the cilia in each ring (TOC score) was expressed as 4 (<25% beating of cilia), 3 (25-50% beating), 2 (50-75% beating), 1 (75-99% beating) or 0 (all beating).…”
Section: Ciliostasismentioning
confidence: 99%
“…Generally, protection is assessed at between 5 and 7 d.p.c. (Ratanasethakul & Cumming, 1983;Gelb et al, 1991;Cook et al, 1999;Alvarado et al, 2003;Terregino et al, 2008;Jackwood et al, 2009;Lim et al, 2012;De Wit et al, 2013), although Darbyshire & Peters (1985) sampled 4 d.p.c. Lambrechts et al (1993) investigated levels of cross-protection in the respiratory tract at 1, 3, 5, 7 and 9 days following aerosol challenge with the B1648 IBV variant in chicks that had been vaccinated with different IBV vaccines.…”
Section: Methods For Performing Protection Studiesmentioning
confidence: 99%
“…For statistical, bird welfare and financial reasons, the choice of the number of chickens per group in experiments is important. The estimation of the required number should be based on the difference in level of protection that it is desirable to detect (effect size), the expected variability of the results between and within groups of chickens, the desired confidence level and the power of the study (De Wit, 2000;De Wit et al, 2013). A meta-analysis performed on the data of 18 IBV vaccinationchallenge experiments performed at The Dutch Animal Health Service, Deventer (GD) showed that the number of birds required per group in order to be able to detect effect sizes of 6.25%, 12.5%, 25% and 50% between groups with 95% confidence (P < 0.05) and 80% power varied greatly from two to 650 depending on both the kind of vaccination programme and on the challenge virus.…”
Section: Methods For Performing Protection Studiesmentioning
confidence: 99%